Gulali Pandan / Amelia Zaidan ... [et al.] - Zaidan, Amelia; Abdull Aziz, Ainul Hayati; Ismail, Nurul Syamilah; Abd Shattar, Noristisarah; Dolah, Siti Noraisah (2021)
Gulali Pandan is a product innovated from a candy known as tepung seman in Malaysia. The product is a small, bite-sized candy infused with pandan leaf in order to extract its flavour, colour and aromatic properties. The objective of this product is to enhance the original plain candy with pandan flavour, use a natural colourant for the appeal, providing a non-messy eating experience while also enlightening the value of tepung seman in other states and expressing cultural identity to outsiders. The product is a combination of pandan flavoured candy, tuile and crushed peanuts with salted caramel granules. The candy is stretched repeatedly by hand to form thin strands, the tuile cookie is baked and formed into a cup shape while the salted caramel is melted, harden and crushed together with peanuts. All of the components are assembled and the finished product is produced. The sensory properties of Gulali Pandan were tested on 30 panels and measured using the Hedonic Test. The evaluation is based on appearance, aroma, colour, sweetness, flavour, aftertaste and overall acceptability. Three variations were presented; (A) natural pandan colour and flavour, (B) artificial green colour and pandan flavour, and (C) natural pandan colour with artificial pandan flavour. The result has shown that sample A is favoured by most repondents. The target market is children, family and tourists. It is unique for its attractive appearance, convenient eating, natural flavouring and suitability as gift or souvenir.